Design and Analysis: Payroll of Accounting Information System - Suryanto, Suryanto (CommIT (Communication and Information Technology) Journal, 2011)
Purpose of the research are to analyze, design, and recommended the payroll of accounting information system that support the internal control to solve the problem. Research methods used are book studies, field studies, and design studies. Fields studies done by survey and interview. The expected result are to give a review about the payroll of accounting information system in the ongoing business process of company and to solve all the weakness in the payroll system, so the company can use the integrated information system in counting of the payroll. Conclusion that can take from the research are there’s some manipulation risk of attendance data and documentation of form still using a manual system and simple data backup. Then, there’s also manipulation risk in allowance cash system and all the report that include in the payroll.Index Terms - Accounting Information System, Payroll